Assessment of Presence of the Phenotypic Characteristics of Polycystic Ovarian Syndrome among Young Adult Girls in a Selected College, Kanchipuram District, Tamil Nadu, India (Medico Legal Update, 2020)
Assessment of presence of the phenotypic characteristic of Polycystic Ovarian Syndrome among youngadult girls in a selected college in Kanchipuram District, Tamil Nadu. The Objectives are to assess thephenotypic characteristics of polycystic ovarian syndrome among young adult girls. To determine theassociation between phenotypic characteristics with selected demographic variables. The conveniencesampling technique was used to select 295 sampling. Validity and Reliability data collection tools wereestablished. The data were collected by self-structured questionnaires. The collected data were tabulated andanalyzed. The findings of the present study Shows that the presence of phenotypic characteristics of PCOSbased on score of hirsutism was estimated to be (39.7%) and based on grading of acne was estimated tobe (66.8%) of young adult girls have mild acne characteristics of PCOS, (13.5%) of young adult girls havemoderate acne characteristics of PCOS.(11.9%) have severe acne characteristics of PCOS and (7.8%) havevery severe acne characteristics of PCOS.There is significant association between the demographic variables and the scoring of hirsutism of youngadult girls in their age, residence, age of menarche, regulation of menstrual cycle, length of menstrualcycle, BMI at p value=